Using a comprehensive audit to identify local context prior to care bundle design and implementation for inadvertent perioperative hypothermia in colorectal surgery. Issue 1 (13th January 2021) - Tanner, Judith; Timmons, Stephen; Bayston, Roger; Adams, Kimberley; Baxendale, Bryn
Abstract : Background: The first step in bundle design or implementation is to identify the problem being addressed. Several validated approaches are recommended to facilitate this. These include using systematic reviews, adverse event triggers and risk assessment tools. However, these methods do not fully take the local context into account, which will limit the effectiveness of the bundle. Aim: This study explores the potential benefit of using a comprehensive audit to identify an organisation's local context prior to designing and implementing a care bundle. Method: A comprehensive audit comprising observations of four patient journeys, interviews with 21 staff and clinical data was carried out at one large National Health Service trust in England. A patient warming care bundle was used as the exemplar. Findings: Each of the three data collection methods identified specific local practices which would be addressed within the planning and implementation stages of a care bundle. These practices would not have been identified through other recommended methods. Conclusion: A comprehensive audit, comprising observations, interviews and clinical data is a successful method to identify local contextual issues prior to care bundle implementation.